Simplify the following:
(a+b)³-a³-b³=?
Answers
Answered by
4
(a + b)³ - a³ - b³
Therefore, the formula used in this question is- (a+b)³=a³ + 3a²b + 3ab² + b³,
= (a³ + 3a²b + 3ab² + b³) -a³ - b³
= a³ + 3a²b + 3ab² + b³ - a³ -b³
= (a³ - a³) + (b³ - b³) + 3a²b + 3ab²
= 3a²b + 3ab²
= 3ab (a + b) Answer.
Answered by
1
Answer:
(a + b)³ - a³ - b³
Therefore, the formula used in this question is- (a+b)³=a³ + 3a²b + 3ab² + b³,
= (a³ + 3a²b + 3ab² + b³) -a³ - b³
= a³ + 3a²b + 3ab² + b³ - a³ -b³
= (a³ - a³) + (b³ - b³) + 3a²b + 3ab²
= 3a²b + 3ab²
= 3ab (a + b) Answer.
Similar questions